Influence of temperature on the adhesion of fibre reinforced polymers to timber surface - Valle, Ângela do; Moraes, Poliana Dias de; Mantovani, Giancarlo Zibetti; Fagundes, Hudson (Ambiente Construído, 2019)
In this paper, experimental results concerning the influence of the temperature on the adhesion of carbon and glass fibre reinforced polymers to timber, in the temperature range from 20 to 80°C, is presented. The shear test of adhesive line and pull-off test of the reinforcement from wood surface were carried out using specimens made of Pinus spp. The results have shown that specimens exposed to a temperature of 80 °C presented residual bond strength means of 34% and 20% of the mean strength at room temperature for carbon fibre reinforced polymer (CFRP) and for glass fibre reinforced polymer (GFRP), respectively.